Effects of movement training based on rhythmic auditory stimulation in cognitive impairment: a meta-analysis of randomized controlled clinical trial - Wang, Ya Nan; Wen, Xiao Ni; Chen, Yu; Xu, Nuo; Zhang, Jing Han; Hou, Xue; Liu, Jing Ping; Li, Ping; Chen, Jia Yu; Wang, Jun Hao; Sun, Xin Yue (Frontiers in Neuroscience, 2024)
Objective According to the World Alzheimer’s Disease Report in 2015,there were 9.9 million new cases of dementia in the world every year. At present, the number of patients suffering from dementia in China has exceeded 8 million, and it may exceed 26 million by 2040.Mild cognitive impairment (MCI) refers to the pathological state of pre-dementia with the manifestation of the progressive decline of memory or other cognitive functions but without decline of activities of daily life. It is particularly important to prevent or prolong the development of MCI into dementia. Research showing effects of rhythmic auditory stimulation based-movement training(RASMT) interventions on cognitive function is also emerging. Therefore, the present meta-analysis briefly summarize findings regarding the impacts of RASMT programs on cognitive impairment. Methods Data from Pubmed, Embase, and Cochrane Library were utilized. The impact of RASMT on cognitive functions was evaluated using indicators such as overall cognitive status, memory, attention, and executive functions. The REVMAN5.3 software was employed to analyze bias risks integrated into the study and the meta-analysis results for each indicator. Results A total of 1,596 studies were retrieved, of which 1,385 non-randomized controlled studies and 48 repetitive studies were excluded. After reviewing titles and abstracts of the remaining 163 articles, 133 irrelevant studies were excluded, 30 studies were downloaded and read the full text. Among 30 articles, 18 articles that did not meet the inclusion criteria were excluded, the other 12 studies were included in this meta-analysis. Utilizing the Cochrane Collaborative Network Bias Risk Assessment Scale, it was found that 11 studies explained the method of random sequence generation, nine studies did not describe allocation concealment, four were single-blinded to all researchers, and eight reported single-blinding in the evaluation of experimental results. In the meta-analysis, the main outcomes showed statistically significant differences in overall cognitive status [MD = 1.19, 95%CI (0.09, 2.29), (p < 0.05)], attention [MD = −1.86, 95%CI (−3.53, −0.19), (p < 0.05)], memory [MD = 0.71, 95%CI (0.33, 1.09), (p < 0.01)], and executive function [MD = −0.23, 95% CI (−0.44, −0.02), (p < 0.05)]. Secondary outcomes indicated no statistically significant differences in verbal fluency [MD = −0.51, 95%CI (−1.30, 0.27), (p = 0.20)], while depression [MD = −0.29, 95% CI (−0.42, −0.16), (p < 0.01)] and anxiety [MD = 0.19, 95% CI (0.06, 0.32), (p < 0.01)] exhibited statistically significant differences. The GRADEpro GDT online tool assessed the quality of evidence for the outcome measures, revealing one low-quality outcome, two moderate-quality outcomes, and one high-quality outcome in this review. Conclusion This study shows that RASMT can improve the general cognitive status, memory, attention and executive function of patients with cognitive impairment. The quality of evidence revealed that MMSE was low, attention and memory were moderate, and executive function was high. The RAMST program (type of exercise: play percussion instruments; time of exercise: 30–60 min; frequency of exercise: 2–3 times/week; duration of exercise: more than 12 weeks) was proved to be more effective in improving cognitive function. However, the sample size is relatively insufficient, the future needs further study. Systematic review registration PROSPERO, identifier: CRD42023483561.